Socio-Cultural Problems of the Malay Community in Singapore and in Penang: A Study of Kilat Senja and Aci Patmabi (Malay Literature, 2014)
The way of life of the Malay community cannot be separated from its traditional kampung or rural life, which forms the earliest template of life as family, community and nation, from the earliest stages to the developments of today.Changes over time have given rise to corresponding changes in the kampung, transforming them into advanced, modern towns and cities. This phenomenon occurred in Singapore and Penang, two cosmopolitan states of the Straits Settlements with close historical links.What occurred in Singapore may be discovered in Penang as well. The phenomena or dilemma of "cultural aridity" in Singapore (Lily Zubaidah Rahim, 2004) may have similarities with the problem of "urban sprawl" in Penang (Norizan Md Nor, 2012). On this premis, initiallythe article discusses Hadijah Rahmat's Kilat Senja (2005). Do the socio-cultural issues of the Malay community in Singapore also occur in Penang? The answer to this question may be explicitly and implicitly resolved in Azmi Iskandar Merican's work, Aci Patmabi (2012). Subsequently the article raises and explores a variety of questions on the course of socio-cultural developments of the Malay community in Singapore and Penang.Keywords: socio-cultural issues, cultural aridity, urban sprawl, Singapore, Penang